Pemberdayaan Remaja Melalui Poster Kesehatan Online di Desa Pulau Harapan Kabupaten Kutai Kartanegara - Rian Hilmawan; Dita Ariana Putri (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
The activity of adolescent empowerment through distribution of online health posters (BARTER KAIN) in Pulau Harapan Village, Kutai Kartanegara District is a program that contains tips on maintaining and increasing body immunity from COVID-19, which disseminated to the virtual world through the teenager community. This program aims as a form of effort to overcome the covid-19 outbreak, because it is important to maintain health so that the body remains vigilant so that the body's immunity does not decrease and the exposure to the virus can be avoided. This program is implemented in Pulau Harapan Village, Kec. Muara Muntai, Kab. Kutai Kartanegara on July 8, 2020 s.d. August 18, 2020 using the youth empowerment method with seven (7) participants. The first step that has been done was searching for data, determining the method, creating relevant poster information, and the last step is to spread information with the youth empowerment model through social media that they are familiar (Whatsapp). The results of this activity are useful for teenagers to improve and pay attention to their body health and be alerted in dealing with the Covid-19 virus outbreak, and finally can spread the information to their rural community.